Homogeneous shrinking/amplifying device and its layered realization - Yang, Chengfu; Huang, Ming; Li, Tinghua; Yang, Jingjing; Mao, Fuchun; Xue, Yuyang (AIP advances, 2019)
Arbitrary regular/irregular shaped electromagnetic shrinking device and amplifying device with homogeneous, non-negative, anisotropic and genetic constitutive parameters are proposed and designed based on linear transformation optics, which provides the flexibility for device designing, and closer to the practical implementation. Furthermore, layered structure based on effective medium theory is utilized to remove the anisotropic property of the proposed device. Simulation results show that when with sufficient layers, both the layered shrinking device and amplifying device behave nearly as perfect as the ideal one. A dielectric or magnetic object placed inside the proposed device will be visually transformed into another object with a bigger/smaller size and different constitutive parameters are figured out clearly, making the proposed device have potential applications in military camouflage or other field of electromagnetic engineering system. The shrinking/amplifying scale is tailored by the ratio of b/c (b and c are the quasi-radius of the arbitrarily shaped polygon). Composing of alternatively isotropic layers with positive material parameters would dramatically reduce the fabrication difficulty and move the device a step further towards the practical application.